(untitled) (Research, Society and Development, 2022)
Objective: The present research analyzed the temporal trend of the suicide mortality rate between age groups, methods of committing suicide, sex and months of the year in the city of Cáceres, in the state of Mato Grosso, between 1996 and 2019. Methodology: This is a sample study, documentary, descriptive, quantitative, focusing on cases of suicide that occurred in Cáceres between 1996 and 2019. The data were retrieved from the website of the Department of Information of the Unified Health System (DATASUS), adopting the International Classification of Diseases (CID-10). The comparisons were analyzed statistically using ANOVA with application of F test, Tukey test and Student test, using a significance level of 5% (p < 0,05). Results: During the 24 years analyzed (1996-2019) it was shown that there were 145 suicides in Cáceres, an average of 6 deaths annually. In the 12 months of the year in the analyzed period, the months of July and December had 18 deaths each, while in November there were five deaths. The highest mortality rate occurred among the elderly (over 80 years old) with a rate of 12,67/100 thousand inhabitants. Males had a higher mortality rate (10.7/100 thousand inhabitants), beings up to 4 times higher than females (2,7/100 thousand inhabitants). The most used method to commit suicide in the period in the city of Cáceres was hanging, corresponding to 60,9%. Conclusion: Thus, the sex and age group that most commit suicide are males and the elderly. Furthermore, the most used method of committing suicide was hanging.